Donald Trump's Speech: Understanding the U.S. Explicit and Implicit Agendas on Iran and the Muslim World - Lalu Isnaeni Rahman; Moh Fauzi Bafadal (Muhammadiyah University of Mataram, 2021)
The United States' war on terror effort, which began after the devastating assaults on the World Trade Center (WTC) and the Pentagon on September 11, 2001, has lasted until now. Even under Trump's presidency, U.S. foreign policy toward the Muslim world, particularly in the Middle East, has had little impact on global political stability. The latest tensions between the U.S. and Iran have proved that the